THE EFFECT OF THERAPEUTIC GROUP THERAPY ON THE DEVELOPMENT OF ADOLESCENT SELF IDENTITY IN ORPHANAGE - Kholifah, Siti; Margono, Hendy Muagiri; Fitryasari, Rizki; Yusuf, Ah; Endang, Hanik; Budiono, Budiono (Universitas Airlangga, 2020)
Introduction: Adolescents living in orphanages experience a lack of self-confidence, withdrawal, lack of interest in learning, lack of communication, and a closed attitude so that it will have a negative impact on cognitive, emotional, and social development. This study aims to determine the effect of Therapeutic Group Therapy (TKT) on the development of adolescent self-identity in orphanages. Methods : The study design was a Quasy experimental pre-post test control group design. The population was 104 children living in orphanages A and B. The research sample was 30 intervention groups and 32 control groups that met the inclusion criteria obtained through purposive sampling. The independent variable is Therapeutic Group Therapy while the dependent variable is self-identity. Data obtained using a questionnaire and analyzed using the Wilcoxon Sign Ranks Test and Mann-Whitney U Test with a significance level âˆ” <0.05. Results : The results of the analysis of the intervention group showed the effect of TKT on self-identity (p = 0.0001). The results of the Mann-Whitney U Statistical Test of self-identity test showed a value of p = 0,0001 ( âˆ” <0.05) meaning that there was an effect of TKT on self-identity between the two groups. Conclusion : TKT is done by health workers can help identify identity status teenagers and can improve self-identity teenager who lived in the orphanage through health education.